Gojek's Responsibility for Loss of Items on Gojek Indonesia's Go-Send Feature - Salsabila Annisa Mahadewi; Heniyatun Heniyatun; Chrisna Bagus Edhita Praja; Bambang Tjatur Iswanto (Borobudur Law and Society Journal, 2024)
The development of new science and technology makes it easy for people to buy and sell online through the Tokopedia marketplace and delivery one day or same day. One of the one-day or sameday deliveries that the Gojek application has is the Gosend feature. Apart from making this feature easier for users, there is also a problem, namely that goods are lost during delivery by service providers from Gojek Indonesia. This research aims to analyze the legal relationship between the parties involved to determine the appropriate legal responsibility of Gojek Indonesia for loss of goods (iPad) as regulated in the Consumer Protection Law. This research uses a normative juridical method with a statutory approach. The research results show that PT. Gojek Indonesia has transferred responsibility for the problem of lost items in the form of iPads purchased through Tokopedia by not fully reimbursing the nominal value of the items lost. So the law should be able to break and provide justice for consumers because of the existence of standard agreements.